Unlocking Drought-Induced Tree Mortality: Physiological Mechanisms to Modeling - Li, Ximeng; Xi, Benye; Wu, Xiuchen; Choat, Brendan; Feng, Jinchao; Jiang, Mingkai; Tissue, David (Frontiers in Plant Science, 2022)
Drought related tree mortality has become a major concern worldwide due to its pronounced negative impacts on the functioning and sustainability of forest ecosystems. Yet, our ability to identify the species that are most vulnerable to drought, and to pinpoint the spatial and temporal patterns of mortality events, is still limited. These limitations arise partially because contemporary land surface models (LSMs) are often unable to predict the response of vegetation to environmental perturbations with sufficient accuracy, especially under stressful conditions such as drought. Significant progress has been made regarding the physiological mechanisms underpinning plant drought response in the past decade, and plant hydraulic dysfunction has emerged as a key determinant for tree death due to water shortage. The identification of pivotal physiological events and relevant plant traits may facilitate forecasting tree mortality through a mechanistic approach, with improved precision. In this review, we 1) summarize current understanding of physiological mechanisms leading to tree death, 2) describe the functionality of key hydraulic traits that are involved in the process of hydraulic dysfunction, and 3) outline their roles in improving the representation of hydraulic function in LSMs. We urge potential future research on detailed hydraulic processes under drought, pinpointing corresponding functional traits, as well as understanding traits variation across and within species, for a better representation of drought-induced tree mortality in models.